Evaluate the Impact of a First Aid Module on the Knowledge and Skills Related to First Aid Management Among Nursing Students at Gian Sagar College of Nursing, Ramnagar, Rajpura, Punjab - Davinder Kaur; Sukhdeep Kaur; Jyoti Dhayia (International Journal of Emergency and Trauma Nursing and Practices, 2025)
Introduction: First aid refers to the immediate and temporary care provided to individuals who are injured, ill, or wounded before professional medical assistance becomes available. Since accidents can occur unexpectedly, having fundamental first aid knowledge is invaluable. It enables individuals to deliver prompt, lifesaving assistance and prevent complications until expert care arrives. Training nursing students in first aid is particularly important, as it equips them to preserve life, prevent further harm, and promote recovery in emergency situations. Aim: The study aimed to assess the effectiveness of a structured first aid training module in improving nursing students’ knowledge and practical skills related to first aid management. The goal was to enable students to respond promptly during emergencies, especially within the “golden hour,” and to empower them to educate the public on first aid practices. Methodology: After obtaining ethical clearance, the study was conducted at Gian Sagar College of Nursing among 65 first-semester nursing students selected through purposive sampling. Data were collected using a self-developed multiple-choice questionnaire to assess knowledge and an OSCE checklist to evaluate skills. Tool validity was confirmed through expert review, and reliability was ensured using the test–retest method. A pre-test was followed by implementation of the training module, and a post-test was conducted seven days later. Data were analyzed using descriptive and inferential statistics. Results: Significant improvements were observed in both knowledge (pre-test mean = 12.85; post-test mean = 17.35; p = 0.001) and skills (pre-test mean = 19.71; post-test mean = 27.57; p = 0.001) following the intervention. Conclusion: The first aid training module effectively enhanced nursing students’ knowledge and skills. Structured first aid education is essential for strengthening competencies and improving the quality of patient care
Keywords: First aid; emergency care; knowledge and skills; nursing students; training module